76.6k views
5 votes
Will anyone please help me with this!Please yo math nerds i need u!

By forming the full square in the formula ax2 + bx + c = 0, verify the formula of the solution of the second power equation. x = -b +/- the growth of b2 -4ac / 2a

Will anyone please help me with this!Please yo math nerds i need u! By forming the-example-1
User Warfield
by
5.9k points

1 Answer

5 votes

Answer:

See below.

Explanation:

ax^2 + bx + c = 0

a(x^2 + b/a x) + c = 0

Completing the square:

a [ (x + b/2a)^2 - b^2/4a^2] + c = 0

a[ (x + b/2a )]^2 - b^2 / 4a + c = 0

a[ (x + b/2a )]^2 = b^2 / 4a - c

Dividing both sides by a:

(x + b/2a )^2 = b^2/4a^2 - c/a

Taking square roots of both sides:

x + b/2a = +/- √ (b^2/ 4a^2 - c/a)

x + b/2a = +/- √ [ ( b^2 - 4ac) / 4a^2 )]

x + b/2a = +/- √ ( b^2 - 4ac) / 2a

Subtracting b/2a from both sides and converting the right side to one fraction:

x = [- b +/- √ ( b^2 - 4ac] / 2a.

User HashDefine
by
5.8k points